Study guides

☆☆

Q: 11 equals 2b plus 17 equals?

Write your answer...

Submit

Still have questions?

Related questions

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

b=7

a + 2b = c a = c - 2b

3Mgo+2B

4

5b + 11 - 2b = 3b + 11

2s-2b= a+b+c-2b simplified that would be a+c-b.

If: a = 2b+c Then: a-c = 2b And: b = (a-c)/2

1.5

a = 2b + c then a - 2b = c ie c = a - 2b

It simplifies to: 3b+17

If this was b exponent 2 (squared) or b^2 for the first b, then it is a quadratic expression. b^2 + 2b - 11 = 88 b^2 + 2b - 99 = 0 (b+11)(b-9) = 0 B = -11 or 9

c= a-2b

a-2b=c

2b+3c

5+3b? :3

a=2b 4b=6c becomes 2b=3c a=3c

I ask my 11 year old son. 2b + 18 = 4b Subtract 2b form each side: 18 = 2b Divide each side by 2: 9 = b which is the same as b = 9, but you knew that, didn't you?

It is an equation and the value of b is 3

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals". There is no visible symbol between " ... equals 4" and "2b plus 1".

11(2b2 + 21)

All the terms in b add to 11, so 11b = 132 making b = 12

Presumably this is an equation in the form of: b+2b-11 = 88 3b = 88+11 3b = 99 b = 33 However, if this was b exponent 2 (squared) or b^2 for the first b, then it is a quadratic expression. b^2 + 2b - 11 = 88 b^2 + 2b - 99 = 0 (b+11)(b-9) = 0 B = -11 or 9

3a + 2b = (3*6) + (2*5) = 18 + 10 = 283a+2b= (3x6)+(2x5)= 18+10=28

Amazing! Exactly the same question was posted here on WikiAnswerslast September 23. What an incredible coincidence!8b + 11 - 3b = 2b + 2That 8b on the left side can be combined with the -3b to make 5b .5b + 11 = 2b + 2Subtract 2b from each side:3b + 11 = 2Subtract 11 from each side:3b = -9Divide each side by 3:b = -3(That's the same answer they got last September.)